Investigating the Effects of Psychological Capital on Turnover Intention - Rivaldi , Erwin; Sadeli, Jimmy (KnE Social Sciences, 2020)
A high level of employee turnover in the company might cause negativity in this company such as decreasing productivity and might take a toll on financial budget. Companies will strive to minimize the level of voluntary employee turnover where possible. PsyCap was explored in many researches related to turnover intention and was positively proven. This study aims to investigate the effects of Psychological Capital (PsyCap on employee turnover intention through three mediating variables. Quantitative methods were used, and this study extracted 257 samples from State-Owned Enterprises (BUMN) engaged in telecommunications in Indonesia. In order to better represent the company as a whole, stratified sampling was used. SPSS software was used to process the data with Process V 3.0 macro as an addition. The results of this study revealed positive & significant relationship of PsyCap towards mediating variables while significant & negative relationship between mediating variables and turnover intention. In addition, there is evidence of mediating effects of PsyCap towards turnover intention through job satisfaction, work engagement and psychological well-being. Keywords: Psychological capital, work engagement, job satisfaction, psychological well-being, turnover intention